YOUTHS AND THEIR CHOICE OF CONTRACEPTIVES TOWARDS AN EFFECTIVE REPRODUCTIVE HEALTH: THE CASE OF EKITI STATE, NIGERIA - Osakinle, E. O.; Babatunde, J. O.; Alade, F. A. (European Scientific Journal, ESJ, 2013)
The study of investigated youth and their contraceptive usage toward reproductive health in Ekiti State. It was a descriptive design of the survey type, the sample was 200 youths drawn from both urban and rural areas that were randomly selected from the 16 LGAs in Ekiti State. The instrument used for the data collection was titled Youth and Contraceptive Usage (YAU). The instrument was personally administered to the respondents by the researchers. The instrument had a reliability coefficient of 0.78 at 0.05 level of significance. The data collected was analyzed using frequency counts and percentages as well as t-test analysis. The two hypotheses raised were tested at 0.05 level. The study revealed that there was a significant difference in education of youths and their contraceptive usage, and no significant difference in the location of youths and their contraceptive usage. It was, therefore, concluded that youths should have access to all forms of contraceptive which will lead to a healthy reproductive living and this should not be seen as a way of making our youths promiscuous, but rather lead to a reduction in the rates of abortion and morbidity among the youths.